REVOLUTIONIZING CALL CENTER OPERATIONS: A DEEP DIVE INTO GENESYS CTI AND SALESFORCE INTEGRATION - Umesh Waghmode (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The combination of Genesys CTI and Salesforce CRM platforms is examined in this technical article, which also looks at how this convergence transforms call center operations. The article looks into the commercial effects, performance optimization techniques, integration mechanisms, and architectural framework of integrating CTI-CRM solutions. According to the research, sophisticated features like real-time customer journey mapping, predictive call routing, and unified agent workspaces significantly increase operational efficiency, customer happiness, and agent productivity. Best practices for implementation, testing procedures, and upcoming trends are also covered in the article, with special attention paid to how omnichannel tactics and artificial intelligence have influenced the development of contact center technologies.